KONSEP DASAR PENGEMBANGAN KURIKULUM PAI MULTIKULTURAL DI SMK PENERBANGAN TECHNO TERAPAN MAKASSAR - SULFIANA, SULFIANA; TANG, MUHAMMAD (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2024)
The aim of writing this article is to examine the basic concepts of developing a multicultural PAI curriculum. This research uses a qualitative research method with a case study approach which will be used in this research to explain the development of a multicultural curriculum in Islamic religious education at the Makassar Applied Techno Aviation Vocational School. This research reveals that multicultural Islamic religious education is intended to achieve a broader goal, namely being able to see the human side that crosses religion and cultural traditions as one unit that has different and similar ideals. And researchers found that the implementation of multicultural-based PAI is defined as an effort to combine cultural values ??with Islamic education. The multicultural PAI curriculum is based on several foundations. This includes theoretical foundations, juridical philosophical foundations, sociological foundations, psychological foundations, normative foundations, and organizational foundations, educational models, emphasis on Islamic values ??such as compassion, mutual assistance, tolerance, respect for diversity, peace, wisdom, humanism, and freedom. , Approaches such as the Historical Approach, Sociological Approach, Cultural Approach, Psychological Approach, Aesthetic Approach, Gender Perspective Approach, and Philosophical Approach are several approaches that can be used to teach religion which are expected to increase students' pluralist-multicultural awareness, Development of a multicultural PAI curriculum in vocational schools The Makassar Applied Techno Flight includes several elements, such as: learning content that reflects the differences in culture, traditions and understanding of the Islamic religion from various regions in Indonesia; use of various student-centered learning approaches; and learning evaluation that focuses on aspects of Islamic attitudes, knowledge and skills. Having a multicultural-based Islamic religious education curriculum will have a positive impact on harmony and tolerance between fellow humans ABSTRAKPenulisan artikel ini bertujuan untuk mengkaji konsep dasar pengembangan kurikulum PAI multikultural. Penelitian ini menggunakan metode penelitian yang digunakan yaitu Kualitatif dengan pendekatan studi kasus akan digunakan dalam penelitian ini untuk menjelaskan pengembangan kurikulum multikultural dalam pendidikan Agama Islam di SMK Penerbangan Techno Terapan Makassar. Penelitian ini mengungkapkan bahwa pendidikan agama Islam multikultural dimaksudkan untuk mencapai tujuan yang lebih luas, yaitu mampu melihat sisi kemanusiaan yang melintasi agama dan tradisi budaya sebagai satu kesatuan yang memiliki cita-cita yang berbeda dan sama. Dan peneliti menemukan bahwa kurikulum PAI berbasis multikultural diartikan sebagai upaya dalam menggabungkan nilai-nilai budaya dengan pendidikan Islam, Kurikulum PAI multikultural didasarkan pada beberapa landasan. Ini termasuk landasan teoritis, landasan filosofis yuridis, landasan sosiologis, psikologis, landasan normatif, dan landasan organisasi, Model pendidikannya, menekankan nilai-nilai Islam seperti kasih sayang, tolong-menolong, toleransi, menghargai keberagaman, perdamaian, kearifan, humanisme, dan kebebasan, Pendekatan seperti Pendekatan Historis, Pendekatan Sosiologis, Pendekatan Kultural, Pendekatan Psikologis, Pendekatan Estetik, Pendekatan Berperspektif Gender, dan Pendekatan Filosofis adalah beberapa pendekatan yang dapat digunakan untuk mengajarkan agama yang diharapkan dapat meningkatkan kesadaran pluralis-multikultural siswa, Pengembangan kurikulum PAI multikultural di SMK Penerbangan Techno Terapan Makassar mencakup beberapa elemen, seperti: konten pembelajaran yang mencerminkan perbedaan budaya, tradisi, dan pemahaman agama Islam dari berbagai daerah di Indonesia; penggunaan berbagai pendekatan pembelajaran yang berpusat pada siswa; dan evaluasi pembelajaran yang berfokus pada aspek sikap, pengetahuan, dan keterampilan agama Islam. Dengan adanya kurikulum pendidikan agama Islam berbasis multikultural akan memberikan dampak yang positif bagi kerukunan dan toleransi antar sesama manusia.